Contributions of Termites (Macrotermes Subhylanus) to Improved Productivity of Indigenous Chicken in Smallholder Farms - Majuma, Caroline (JOOUST, 2023)
A growing world population coupled with changing socio-demographics continues to place intense pressure on the world’s resources to provide not only more but also diverse food and feed types. Increased demand for animal-based protein resulting from the growing population will have a negative impact on the already stretched environment. More sustainable and alternative sources of protein both for human and animal consumption should be prioritized. Most of the world’s population reside in the rural areas and directly depend on the Indigenous Chicken (IC) as a source of both protein and income. There are however concerns on the productivity of IC since they are mostly left to scavenge bringing the challenges of poor nutrition. In an effort to improve the productivity of the IC, farmers have deliberately collected and fed termites to IC. This study outlined the utilisation of Macrotermes subhylanus, a wingless termite species as a source of alternative protein to Indigenous chicken for improved food and nutrition security among small holder famers. The aim of the study was to generate knowledge that would promote the utilization of termites as feed to IC. The specific objectives were to determine the demographic characteristics that influence the use of termites and to determine the nutrient content of Macrotermes subhylanus. The study employed a descriptive cross-sectional survey where multistage proportionate and simple random techniques were used to select the 218 respondents. Chi-square tests and logistic regression were used to analyze the collected data using R(version4.0.2) statistical software. Macrotermes subhylanus were collected using trapping method, sundried and subjected to proximate and mineral analysis. Proximate analysis was done using the official methods described by AOAC 2000. Calcium was determined spectrophotometrically by using Shimadzu atomic absorption spectrophotometer model AA-6200, while Phosphorus was determined using molybdovanadate reagent and UV visible spectrophotometer. Of the total number of respondents, 142(66.7%) used termites for feeding IC, while 71(33.3 %) did not. Occupation and education level of the respondents had a significant association with termite usage (χ2 =7.319, p-value = 0.042) 2 and (χ= 15.241, p-value = 0.004) respectively. Dry matter, Moisture, Crude Fiber, Crude Fat, Crude Protein and Ash were 91.5%, 8.5%, 24.25%, 4.55%, 37.7%, and 19.95% respectively. Phosphorus and Calcium levels were 1.85mg/100g and 38.625mg/100g, respectively. It was concluded that Macrotermes subhylanus are rich in protein and calcium and could be used as protein supplement for IC.
Keywords: Termites (Macrotermes Subhylanus); Indigenous Chicken; Smallholder Farms